2008
DOI: 10.1590/s0101-20612008000100017
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento e seleção de fungos filamentosos termorresistentes em etapas do processo produtivo de néctar de maçã

Abstract: ). Os ascósporos destes fungos podem permanecer em estado de dormência em restos de frutas apodrecidas e no solo ( RAJASHEKHARA; SURESH; ETHIRAJ, 2000;TOURNAS;TRAXLER, 1994), necessitando ativação térmica para germinarem, o que normalmente corresponde aos processamentos térmicos comerciais aplicados a produtos de frutas (ENIGL; KING Jr.; TOROK, 1993).Estes microrganismos ainda são conhecidos por produzirem várias micotoxinas, como a patulina, durante seu desenvolvimento nos produtos de frutas, o que representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Another study also found this HRM from a concentrated apple juice process in a step after pasteurization (Salomão et al , 2008b). …”
Section: Discussionmentioning
confidence: 78%
“…Another study also found this HRM from a concentrated apple juice process in a step after pasteurization (Salomão et al , 2008b). …”
Section: Discussionmentioning
confidence: 78%
“…Microorganisms and preparation of spore suspension B. fulva IOC 4518 strain was isolated from apple juice concentrate by Salomão et al (2008) and N. fischeri was isolated and identified in samples taken from an apple nectar processing line by Salomão (2002). The preparation of B. fulva and N. fischeri spores started by the pre-sporulation in Petri dishes containing Potato Dextrose Agar (PDA) media (pH 3.5) for 7 days at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, heat resistant fungi have been isolated from different commercial juices such as, pineapple [33], apple [34,35], caja, umbu (typical Brazilian fruits) [36], passion fruit [37], and Byssochamys species are the most frequent. In the USA, the most common cause of beverage spoilage is B. spectabilis [38].…”
Section: Paecilomyces In Foodmentioning
confidence: 99%